Rock and metal labor in Andean cultures - Bueno Mendoza, Alberto (2011)
Current archaeological studies of the origins of metal working and its technology involves many difficulties, because the old mines have almost disappeared before mining industrialization since the sixteenth century (Spanish invasion) or the operation of the laundry since then continue to the present.